2009
DOI: 10.1007/s10532-008-9244-9
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic ethylene glycol degradation by microorganisms in poplar and willow rhizospheres

Abstract: Although aerobic degradation of ethylene glycol is well documented, only anaerobic biodegradation via methanogenesis or fermentation has been clearly shown. Enhanced ethylene glycol degradation has been demonstrated by microorganisms in the rhizosphere of shallow-rooted plants such as alfalfa and grasses where conditions may be aerobic, but has not been demonstrated in the deeper rhizosphere of poplar or willow trees where conditions are more likely to be anaerobic. This study evaluated ethylene glycol degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In comparison, the utilization of organic pollutants or industrial waste as sacrificial reagents, followed by decomposing them into environmentally friendly products, has been identified as a clean and economical method. 30,31 For example, ethylene glycol is produced in large amounts as industrial and civil waste, [32][33][34] and has been proven to be an effective electron donor for photocatalytic hydrogen generation. 35 On the other hand, for effective H 2 -production, noble metals, such as Pt, 30 Au 31 and Pd, 36 must be used in most photocatalytic systems as a co-catalyst loaded onto the surface of TiO 2 to promote the separation and transfer of charge carriers from the TiO 2 to the loaded noble metals where H + is reduced to hydrogen molecules.…”
Section: Broader Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the utilization of organic pollutants or industrial waste as sacrificial reagents, followed by decomposing them into environmentally friendly products, has been identified as a clean and economical method. 30,31 For example, ethylene glycol is produced in large amounts as industrial and civil waste, [32][33][34] and has been proven to be an effective electron donor for photocatalytic hydrogen generation. 35 On the other hand, for effective H 2 -production, noble metals, such as Pt, 30 Au 31 and Pd, 36 must be used in most photocatalytic systems as a co-catalyst loaded onto the surface of TiO 2 to promote the separation and transfer of charge carriers from the TiO 2 to the loaded noble metals where H + is reduced to hydrogen molecules.…”
Section: Broader Contextmentioning
confidence: 99%
“…Photocatalytic H 2 -production activity on various samples was evaluated under UV-LED irradiation using ethylene glycerol as a scavenger. [32][33][34][35] Control experiments indicated that no appreciable hydrogen production was detected in the absence of either irradiation or photocatalyst, suggesting that hydrogen was produced by photocatalytic reactions on photocatalyst. Fig.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…Two mechanisms for removal of ethylene glycol (microbial degradation in the rhizosphere and uptake by the trees through evapotranspiration) have been identified [34,35]. Based on these results, it is very probable that similar mechanisms can be effective for removal of other organic compounds.…”
Section: Environmental Benefitsmentioning
confidence: 97%
“…3 Another study documented the anaerobic biodegradation of ethylene glycol by microbes in the rhizosphere of poplar and willow trees with complete conversion of ethylene glycol using nitrate and sulphate as terminal electron acceptors. 4 Psychotropic bacterium such as Pseudomonas fluorescens has also been reported to degrade ethylene glycol with the substrate inducing the expression of ethylene glycol shock and acclimation proteins. 5 Besides degradation of ethylene glycol, there have also been studies on the biosynthesis of the molecule.…”
Section: Background Analysismentioning
confidence: 99%